2019
DOI: 10.2196/11852
|View full text |Cite
|
Sign up to set email alerts
|

High-Fidelity Prototyping for Mobile Electronic Data Collection Forms Through Design and User Evaluation

Abstract: Background Mobile data collection systems are often difficult to use for nontechnical or novice users. This can be attributed to the fact that developers of such tools do not adequately involve end users in the design and development of product features and functions, which often creates interaction challenges. Objective The main objective of this study was to assess the guidelines for form design using high-fidelity prototypes developed based on end-user preferences. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
1
0
1
Order By: Relevance
“…Selain itu, prototipe hi-fi juga memberikan pengalaman yang hampir serupa dengan produk final kepada pengguna, sehingga membantu mereka dalam mengevaluasi potensi penggunaan produk di tempat kerja mereka. Dengan demikian, prototipe hi-fi sangat berperan dalam memberikan informasi yang lebih lengkap dan memfasilitasi penilaian pengguna terhadap kemungkinan penggunaan produk [10].…”
Section: Gambar 11 Diagram User Flow Buat Catatan Dan Konversiunclassified
“…Selain itu, prototipe hi-fi juga memberikan pengalaman yang hampir serupa dengan produk final kepada pengguna, sehingga membantu mereka dalam mengevaluasi potensi penggunaan produk di tempat kerja mereka. Dengan demikian, prototipe hi-fi sangat berperan dalam memberikan informasi yang lebih lengkap dan memfasilitasi penilaian pengguna terhadap kemungkinan penggunaan produk [10].…”
Section: Gambar 11 Diagram User Flow Buat Catatan Dan Konversiunclassified
“…Recent studies have shown that text messaging (SMS) as a mobile intervention in antenatal care can quadruple or increase the number of users of WHO recommendations and also reduce mortality during pregnancy (7). In other words, global coverage of good quality-based care worldwide could prevent approximately 113,000 maternal deaths, 531,000 fetal deaths, and 1.3 million infant deaths per year by 2020 (18).…”
Section: Introductionmentioning
confidence: 99%